FORMATION OF THE SYSTEM OF IMPLEMENTATION OF THE CRISIS MANAGEMENT MECHANISM BASED ON THE EXAMPLE OF MINING ENTERPRISES - Stovpnik, Stanislav; Temchenko, Oleksandr; Breher, ZHanna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
In conditions of economic instability, the problem of implementation of the crisis management mechanism in modern industrial enterprises is of particular importance. The problem of the research is to develop recommendations as a result of the analysis of the financial condition of industrial enterprises of Ukraine in an unstable economy. The paper discusses the features of the implementation of anti-crisis programs in modern mining and processing enterprises with the determination of the share of equity for the difficult conditions of production and economic activity. The aim of the research is to analyze the financial condition of industrial companies and develop recommendations to overcome the crisis. Taking into account the specifics of mining and processing enterprises, in order to overcome the crisis and solve the problems of production for the effective use of raw materials, the paper identified logistics and financial opportunities, made a forecast of the financial condition in the near future and determined the probability of termination of their activities, as well as developed sound recommendations in the context of the implementation of the crisis management mechanism at iron ore plants. The main methods used in the study: analysis, synthesis, comparison, models for assessing the probability of bankruptcy.